Immunomodulatory Properties of Leishmania Extracellular Vesicles During Host-Parasite Interaction: Differential Activation of TLRs and NF-κB Translocation by Dermotropic and Viscerotropic Species - Nogueira, Paula Monalisa; de Menezes-Neto, Armando; Borges, Valéria M.; Descoteaux, Albert; Torrecilhas, Ana Claudia; Xander, Patrícia; Revach, Or-Yam; Regev-Rudzki, Neta; Soares, Rodrigo Pedro (Frontiers in Cellular and Infection Microbiology, 2020)
Leishmania infection causes considerable human morbidity and may develop into a deadly visceral form in endemic regions. The parasite infects macrophages where they can replicate intracellularly. Furthermore, they modulate host immune responses by using virulence factors (lipophosphoglycan, glycoprotein-63 and others) that promote survival inside the cells. Extracellular vesicles (EVs) released by parasites are important for cell-cell communication in the proinflammatory milieu modulating the establishment of infection. However, information on the ability of EVs from different Leishmania species to modulate inflammatory responses is scarce, especially from those species causing different clinical manifestations (visceral versus cutaneous). The purpose of this study was to compare macrophage activation using EVs from three Leishmania species from New World including L. infantum, L. braziliensis and L. amazonensis. EVs were released from promastigote forms, purified by ultracentrifugation and quantitated by Nanoparticle Tracking Analysis (NTA) prior to murine macrophage exposure. NTA analysis did not show any differences in the EV sizes among the strains. EVs from L. braziliensis and L. infantum failed to induce a pro-inflammatory response. EVs from both L. infantum WT and LPG-deficient mutant (LPG-KO) did not show any differences in their interaction with macrophages, suggesting that LPG solely was not determinant for activation. On the other hand, EVs from L. amazonensis were immunomodulatory inducing NO, TNF-α, IL-6 and IL-10 via TLR4 and TLR2. To determine whether such activation was related to NF-B p65 translocation, THP-1 macrophage cells were exposed to EVs. In the same way, only EVs from L. amazonensis exhibited a highly percentage of cells positive for NF-B. Our results suggest an important role of EVs in determining the pattern of immune response depending on the parasite species. For L. infantum, LPG was not determinant for the activation.